Methodology for analyzing socio-environmental vulnerability applied to rural settlements - Francielle Rodrigues de Oliveira; Roberto Avelino Cecílio; Sidney Sara Zanetti (Ambiente & Sociedade)
Abstract Studies on vulnerability that include both environmental and social aspects, are important tools to support decision-making in the face of socio-environmental problems. The Agrarian Reform settlements have a diversity of social characteristics in addition to being located in environmental systems with specific limitations. Therefore, this research aimed to develop a method to identify the socio-environmental vulnerability of the settlements. The Socio-Environmental Vulnerability Index was created from environmental and social indicators. The SPI revealed severe to extreme droughts mainly between 2014 and 2016. Three settlements were classified with moderate IVS and six with high IVS. The settlements showed little variation in environmental vulnerability. The IVUSA ranged from moderate to high. Settlements with high socio-environmental vulnerability also showed high social vulnerability, while areas with moderate vulnerability exhibited lower indices of both social and environmental vulnerability.